Faktor-Faktor yang Mendukung dan Menghambat Pemeriksaan dan Rehabilitasi Cedera pada Atlet Futsal: Study Kasus One Lotus Personal Therapy - Weni Dwi Apilia; Kurniati Rahyuni; Nurrul Riyad Fadhli (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is based on phenomena that occur in the field which show the supporting and inhibiting factors for athletes in carrying out injury examinations and rehabilitation. The aim of this research is to determine the factors that support and hinder athletes in carrying out injury examinations and rehabilitation. The type of research is qualitative case study research by interviewing 8 athletes who are One Lotus Therapy clients and 3 rehabilitation practitioners who work at One Lotus Personal Therapy. The data collection method used was semi-structured interviews, while data analysis used inductive approach analysis techniques or content analysis. The results of the analysis show that the factors that support injury examination and rehabilitation are (a) encouragement factors from teammates (b) injury factors that do not heal (c) motivation factors from oneself, while the inhibiting factors are (a) factor of lack of knowledge about rehabilitation practitioners (b) injury diagnosis factor (c) distance factor. It is hoped that this research can add insight into dealing with sports injuries.